Impact of product differentiation, marketing Investments and brand equity on pricing strategies: a brand level investigation - Davcik, N.; Sharma, P. (European Journal of Marketing, 2015)
Prior research explores the individual impact of brand equity and new product development on firms’ marketing performance but there is little work that takes a holistic view of their combined influence. This paper uses an aggregate data set for 735 fast moving consumer goods (FMCG) brands from Nielsen to explore the combined influence of brand equity, marketing investment and product differentiation on differences in pricing among small and medium enterprises (SME), multinational companies (MNC) and retailers (private labels). Using a cluster analysis, it is shown that premium price is positively associated with innovation and company type. Managerial implications of the findings are discussed along with future research directions.